A Banana Republic? Trust in Electoral Institutions in Western Democracies - Evidence from a Presidential Election in Austria - Niklas Potrafke; Felix Rösel (Center for Economic Studies and ifo Institute (CESifo), 2016)
We examine the extent to which political scandals influence trust in electoral institutions in established Western democracies. The second ballot of the 2016 Presidential election in Austria needed to be repeated because of inconsistencies in individual electoral districts (scandal districts). In particular, postal votes were counted carelessly. We use a difference-indifferences approach comparing the regular and the repeated round of the second ballot, and examine whether voter turnout, postal voting, invalid voting and the vote shares of the candidates changed in scandal districts. Postal voting declined, but the results do not show that districts with inconsistencies differ regarding voter turnout, postal voting, invalid voting, and vote shares of the candidates. Voters' trust in electoral institutions does not seem to depend on individual failing local administrations.
Keywords: D72; D02; Z18; P16; 330; presidential elections; political scandals; trust; voter turnout; candidate vote share; natural experiment